2015
DOI: 10.1016/j.ajog.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits ovarian cancer growth and increases sensitivity to paclitaxel in mouse models

Abstract: OBJECTIVE There is increasing pre-clinical evidence indicating that metformin, a medication commonly used for type 2 diabetes, may protect against cancer. Motivated by this emerging evidence we asked two questions: (a) can metformin prevent ovarian cancer growth by altering metabolism, and (b) will metformin increase sensitivity to chemotherapy. STUDY DESIGN The effect of metformin in ovarian cancer was tested in vitro and by using two different mouse models. In vitro, cell lines (n=6) were treated with metf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 49 publications
6
103
0
1
Order By: Relevance
“…Metformin therapy weakens the risk of glioma-initiating cells (48), and inhibits ovarian cancer by increasing sensitivity to cisplatin (49,50), endometrial cancer through changes in Ki-67 proliferation (51-53), and breast cancer (54,55) and non-small cell lung carcinomas (56,57). Laboratory studies on breast cancer have shown that metformin increases the mean life span by 8% and mammary adenocarcinoma latency by 13.2% (P<0.05) in HER2/neu mice (58).…”
Section: Discussionmentioning
confidence: 99%
“…Metformin therapy weakens the risk of glioma-initiating cells (48), and inhibits ovarian cancer by increasing sensitivity to cisplatin (49,50), endometrial cancer through changes in Ki-67 proliferation (51-53), and breast cancer (54,55) and non-small cell lung carcinomas (56,57). Laboratory studies on breast cancer have shown that metformin increases the mean life span by 8% and mammary adenocarcinoma latency by 13.2% (P<0.05) in HER2/neu mice (58).…”
Section: Discussionmentioning
confidence: 99%
“…Metformin intake is associated with better survival in ovarian cancer (Kumar et al, 2013), reduces ovarian cancer risk in Taiwanese women with type 2 diabetes mellitus (Tseng et al, 2015), targets ovarian cancer stem cells in vitro and in vivo (Shanka et al, 2012), limits the adipocyte tumor promoting effect on ovarian cancer (Tebbe et al, 2014), prevents aggressive ovarian cancer growth driven by high energy diet (Wahab et al, 2015). Moreover, metformin inhibits ovarian cancer growth and increases sensitivity to paclitaxel in mouse models (Lengyel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As seen in previous studies of metformin in OC mouse models [73][74][75], metformin inhibited tumor growth in the KpB mouse model. However, while metformin inhibited tumor growth in both the HFD-and LFD-fed mice, metformin had a more potent effect in the HFDfed mice (60% decrease in HFD-fed mice, 32% decrease in LFD-fed mice).…”
Section: Discussionmentioning
confidence: 63%